2011
DOI: 10.1002/ca.21177
|View full text |Cite
|
Sign up to set email alerts
|

The femoral calcar: A computed tomography anatomical study

Abstract: The femoral calcar is a dense internal septum reaching from the femoral neck to the distal part of the lesser trochanter. Our study aimed at providing an exhaustive radio-anatomical description of this structure. One hundred pelvic computed tomography examinations were retrospectively selected to bilaterally evaluate the shape, dimensions, and density of the femoral calcar. Then, its relation to the femoral cavity was assessed by recording the dimensions of the medullary canal at the level of the greatest leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…A positive correlation between the CF and postoperative stem anteversion has been reported in OA patients [10, 11, 15]. In this study, we also found a strong positive correlation between postoperative stem anteversion and both CF-LFN and CF-CLT in the CF group, supporting that the CF angle influences the version of the effective femoral cavity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A positive correlation between the CF and postoperative stem anteversion has been reported in OA patients [10, 11, 15]. In this study, we also found a strong positive correlation between postoperative stem anteversion and both CF-LFN and CF-CLT in the CF group, supporting that the CF angle influences the version of the effective femoral cavity.…”
Section: Discussionsupporting
confidence: 87%
“…The calcar femorale (CF) plays an essential role in the initial stability and alignment of femoral stems [10] and has been reported to reduce torsional micromotion between the stem and host bone [11]. Several studies investigated the relationship between CF, femoral anteversion (FA) at various levels, and final stem anteversion using computed tomography (CT) scan in patients with primary osteoarthritis [9, 1214].…”
Section: Introductionmentioning
confidence: 99%
“…The calcar femorale can take various shapes, lengths, and thicknesses. Le Corroller et al 18) classified the shape of the calcar femorale into three types among normal hips without osteoarthritis. A ridge type was present in 17.0% of hips, a spur type in 66.5%, and a septum type in 16.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the original classification of calcar femorale by Le Corroller et al 18) does not offer sufficient reproducibility or reliability due to the lack of objectivity of the classification. We therefore classified the shape of the calcar femorale using a modification of the classification described by Le Corroller et al 18) into “ridge type” for a short and thick structure (< 9 mm), “septum type” for a thin and long structure (≥ 13 mm), and “spur type” for an intermediate structure, for better objectivity. In order to further improve reliability, calcar femorale should be classified after correcting for patient height, not simply by considering its length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation